The PARENTS PATTERNS AND THE CHARACTERISTICS OF YOUTH WITH THE IMPLEMENTATION OF YOUTH DEVELOPMENT TASKS IN MERAK URAK JUNIOR HIGH SCHOOL TUBAN - Teresia Retna Puspita Dewi; Wahyuningsih Triana Nugraheni; noer saudah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2019)
ABSTRACT In this period of life, adolescents was required to complete special development tasks as a prerequisite for fulfillment and happiness of their lives. There are still many teenagers who had not been optimal in their development tasks. The aim of the study was to explain the parenting style and characteristics of adolescents with the implementation of the task of adolescent development. The study design used observational analytic, with a cross sectional approach. The study population was 8th grade students in Merak Urak Junior High School, Tuban, 2017/2018 academic year totaling 245 students. The total sample was 152 students taken by simple random sampling. Data collection used a questionnaire.Simultaneous test results indicate that there were one parenting variable with a significance value of p-value of 0.000 <0.05, H1 is accepted, meaning that there is a significant effect of parenting toward the implementation of adolescent development tasks with an influence coefficient of 1.593 and OR 4.920 . While the age and gender variables simultaneously there is no influence on the implementation of the development task. Parents as one family member has a major role in achieving the implementation of the task of developing adolescents, because parents are the closest people to interact and face to face with adolescents so that all problems related to the completion of the task of adolescent development can be overcome by good communication between adolescents and people old. Keywords: Parenting, developmental tasks, adolescents